2015
DOI: 10.1016/j.rboe.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Arthroplasty of the distal ulna distal in managing patients with post-traumatic disorders of the distal radioulnar joint: measurement of quality of life

Abstract: ObjectiveTo measure the quality of life and clinical–functional results from patients diagnosed with osteoarthrosis of the distal radioulnar joint who underwent surgical treatment using the technique of total arthroplasty of the ulna, with a total or partial Ascension® prosthesis of the distal ulna.MethodsTen patients were evaluated after 12 months of follow-up subsequent to total or partial arthroplasty of the distal ulna. All of them presented post-traumatic osteoarthrosis and/or chronic symptomatic instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Aita et al evaluated a case series of 10 patients in which one patient was treated with partial ulnar head arthroplasty and 9 with total ulnar head arthroplasty. 37 Overall, the 10 patients in this study showed range of motion in pronosupination 174.5 AE 7.15 degrees. VAS of 2.13, and palmar grip strength at 90.7% of unaffected side after 1-year follow-up.…”
Section: Implant Arthroplastymentioning
confidence: 62%
“…Aita et al evaluated a case series of 10 patients in which one patient was treated with partial ulnar head arthroplasty and 9 with total ulnar head arthroplasty. 37 Overall, the 10 patients in this study showed range of motion in pronosupination 174.5 AE 7.15 degrees. VAS of 2.13, and palmar grip strength at 90.7% of unaffected side after 1-year follow-up.…”
Section: Implant Arthroplastymentioning
confidence: 62%
“…Historically, advanced arthrosis of the DRUJ was commonly treated with complete or parcial resection of the ulnar head (Darrach procedure) or a combination of this and DRUJ arthrodesis, as in the Sauvé-Kapandji procedure [ [2] , [3] , [4] , [5] ]. Despite satisfactory results in some patients, especially older ones, these techniques are associated with high risk of wrist instability and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Another method of treating these disorders is replacing the ulnar head with an artificial prosthesis. Although seen with some scepticism at the beginning, there is now a significant amount of published data regarding very satisfactory mid-term results of these implants [ [1] , [2] , [3] , 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sintomatologia também inclui dor, fraqueza e dificuldades na execução das atividades da vida diária, gerando grande impacto na qualidade de vida dos pacientes. Por esta razão, um tratamento adequado é necessário para restabelecer essas perdas de forma parcial ou total [1][2][3][4][5] .…”
unclassified